IMPLEMENTASI AKUNTANSI SYARIAH UNTUK RUMAH SAKIT - Fauziah (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
Sharia economy that used to be synonymous with sharia financial institutions such as sharia banking, sharia insurance, and sharia capital market, now the concept of sharia is applied to other business sectors even to services such as the concept of sharia tourism with the hotel sharia and the latest is hospital services concept of sharia. Although the existence of hospitals already known at first, but the concept of hospitals that are in service and financial statements based on the concept of sharia is just beginning to apply. Implementation of sharia hospitals and sharia financial reporting is also regulated in SAK Sharia. SAK that regulates sharia financial under PSAK 101 Presentation of Sharia Financial Statements (revised 2016). The existence of a hospital is similar to other companies / organizations, it has a function and part to carry out service activities to the community. Each function has responsibility and control system. The function of sharia accounting system in hospitals to provide accountable and transparent financial information as the basis for proper decision making and planning ahead. So the hospital has Value Added. The hospital needs to implement a sharia accounting system in order to eliminate discrimination between economic activity and worship. Hospitals have a unique accounting system because in addition to running a business, also carry out social activities.